2015
DOI: 10.1021/acssynbio.5b00197
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Reassignment of a Frequent Serine Codon in Wild-Type Escherichia coli

Abstract: Expansion of the genetic code through engineering the translation machinery has greatly increased the chemical repertoire of the proteome. This has been accomplished mainly by read-through of UAG or UGA stop codons by the noncanonical aminoacyl-tRNA of choice. While stop codon read-through involves competition with the translation release factors, sense codon reassignment entails competition with a large pool of endogenous tRNAs. We used an engineered pyrrolysyl-tRNA synthetase to incorporate 3-iodo-l-phenylal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…[23] Recently, O'Donoghue et al showed that the machinery of selenocysteine can be modulated to recognize 58 of the 64 naturally occurring codons, in many cases completely outcompeting the endogenous tRNA, although other codons resulted in ambiguous translation. [24] Söll and co-workers showed that the serine sense codon AGU can be reassigned to 3-iodo-Lphenylalanine (3-I-Phe), [25] while Kwon and co-workers recently showed that it is possible to achieve ambiguous reading of the leucine UUG codon with 2-naphthylalanine. [26] In general, amino acids encoded by several codons (e.g., serine, leucine and arginine) offer more chances to be recoded since the wobble pairing at the 3 rd base could be outcompeted by a more energetically favorable WatsonCrick base pairing with the orthogonal tRNA.…”
Section: "Rewiring" the Genetic Code: Sense Codons Reassignmentmentioning
confidence: 99%
“…[23] Recently, O'Donoghue et al showed that the machinery of selenocysteine can be modulated to recognize 58 of the 64 naturally occurring codons, in many cases completely outcompeting the endogenous tRNA, although other codons resulted in ambiguous translation. [24] Söll and co-workers showed that the serine sense codon AGU can be reassigned to 3-iodo-Lphenylalanine (3-I-Phe), [25] while Kwon and co-workers recently showed that it is possible to achieve ambiguous reading of the leucine UUG codon with 2-naphthylalanine. [26] In general, amino acids encoded by several codons (e.g., serine, leucine and arginine) offer more chances to be recoded since the wobble pairing at the 3 rd base could be outcompeted by a more energetically favorable WatsonCrick base pairing with the orthogonal tRNA.…”
Section: "Rewiring" the Genetic Code: Sense Codons Reassignmentmentioning
confidence: 99%
“…reported the first example of breaking the degeneracy of the genetic code by incorporating ncAAs in response to one of two Phe codons (28). Recent reports have described the incorporation of ncAAs in response to reassigned rare arginine, isoleucine and serine codons (2934). …”
Section: Introductionmentioning
confidence: 99%
“…That tRNA Pyl is a natural amber suppressor and that PylRS largely interacts with the G73, G1:C72, and unique core tertiary motifs of tRNA Pyl but not with its anticodon [61, 62] has made the PylRS•tRNA Pyl pair popular in GCE applications in both bacteria and eukaryotes [1, 63]. More importantly, the lack of tRNA anticodon recognition of PylRS has been exploited to not only incorporate ncAAs in response to stop codons but also in response to sense [64] and quadruplet codons [65]. …”
Section: Trna Dictates Orthogonality: Recognition By Aarssmentioning
confidence: 99%